Atmospheric Processing at the Sea‐Land Interface Over the South China Sea: Secondary Aerosol Formation, Aerosol Acidity, and Role of Sea Salts. Issue 5 (7th March 2022) - Wang, Guochen; Chen, Jia; Xu, Jian; Yun, Long; Zhang, Mingdi; Li, Hao; Qin, Xiaofei; Deng, Congrui; Zheng, Haitao; Gui, Huaqiao; Liu, Jianguo; Huang, Kan
Abstract: Sea salts act as an important medium for atmospheric processing. One intensive field campaign in the September–October period of 2019 was conducted at a subtropical coastal site over the South China Sea. Unexpected high concentrations of acidic gaseous precursors were observed, yielding high sulfate in PM2.5 . Na +  ranked as the third highest inorganic species, about half of NH4 + . Significant cation deficiency was found due to the ammonia‐poor environment. Diel patterns of most air pollutants from land breeze were stronger than that from marine breeze and presented pronounced unimodal distributions, which were ascribed to complex chemical processing mixed with regional transport. Thermodynamic equilibrium model (ISORROPIA II) simulation revealed sea salts could be internally mixed with fine particle secondary species and suggested evident multiphase reactions on sea salts. The simulated aerosol pH reached as low as 1.63 ± 0.50, which was related to high sulfate, insufficient alkaline species, and low aerosol liquid water content. During a continuous sea breeze episode, SO4 2− was underpredicted by 2.89 ± 3.85 μg m −3 if Na + was not considered in ISORROPIA simulation. The retrieved Na +  ‐related ion pairs (NaCl, NaHSO4, and Na2 SO4 ) accounted for about one‐fourth of the total inorganic aerosols. This study highlighted that intense atmospheric processing on sea salts occurred in fine particles and the mixing state between sea salts and other aerosol species should be considered in aerosol acidity prediction and secondary aerosol formation in coastal regions. Key Points: Sea salts were internally mixed with the secondary species even in fine particle, suggesting evident multiphase reactions on sea salts Aerosol pH was very low at the land‐sea interface and it depended on the relative strengths of sea salts versus terrestrial ammonia emissions The retrieved chemical forms of SO4 2− contained a substantial contribution from bisulfate, mainly in the form of NaHSO4 and NH4 HSO4